Formulation of Burger Patty Analog of White Oyster Mushroom (Pleurotus ostreatus) and Red Bean (Phaseolus vulgaris L) With Several Type of Binder: Formulasi Patty Burger Analog Jamur Tiram Putih (Pleurotus ostreatus) dan Kacang Merah (Phaseolus vulgaris L) dengan Beberapa Jenis Pengikat - Kenanga Putri Utami; Vivi Nuraini; Nanik Suhartatik (Fakultas Sains dan Teknologi Unisri, 2024)
Burger patty analog is a processed imitation meat based on plant ingredients. This experiment used white oyster mushroom puree and red bean puree with various types of binder. This study was aimed at determining the chemical and organoleptic characteristics of burger patty analog that are high in protein and fiber, as well as determining the analog burger patty formulation that is most preferred by panelists. The research used a factorial Completely Randomized Design (CRD) with two factors, namely the ratio of white oyster mushroom puree and red bean puree (70: 30, 60; 40, 50: 50) and variations in the type of binder (sago flour, tapioca flour, cornstarch). The results showed that the formulation of 50% white oyster mushroom puree and 50% red bean puree with cornstarch had a high protein content of 6.68%. Formulation of 70% white oyster mushroom puree and 30% red bean puree with sago flour has the highest crude fiber content of 7.64%. The burger patty analog formulation which the most liked by panelists was at 60% of white oyster mushroom puree and 40% red bean puree formulation using tapioca flour, resulting in an overall favorability score of 3.62 (neutral). This study resulted in low protein. Patty burger analog had low fat content, in added as an alternative for people who cannot consume meat.